Electrical Resistivity Survey of the Gunung Anyar Mud Volcano - Primasari Cahya Wardhani; Bagas Aryaseta; Nia Dwi Puspitasari (Universitas Islam Sultan Agung, 2022)
The past oil and natural gas drilling activities have been presumed to cause a Mud Volcano phenomenon. The Mud Volcano potentially danger its surroundings, including the inhabitants. Thus, mapping the zone will be essential to have a mitigation plan. One of the potential Mud Volcanoes is the Gunung Anyar Mud Volcano. By using a resistivity survey, this research aims to obtain the subsurface structure of the Gunung Anyar Mud Volcano. The results show that very low resistivity values are located at the top of the soil structure with 0 to 4 meters depth. This soil structure is believed to be a manifestation of a mud volcano in the form of moistened clay associated with salt water. At subsequent depths, 4 to 5.5 meters from the top, is a layer of sandy clay. It is characterized by moderate to high resistivity values. At a depth of 5.5 to 10.5 meters, the resistivity value is very high. This sandstone layer is most likely a native subsoil formation in the Gunung Anyar area.